1963
DOI: 10.1111/j.1748-1716.1963.tb02609.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thyroxine on the Hydroxyproline in Rat Urine and Skin

Abstract: The effect of L‐thyroxine on the metabolism of collagen in rats was studied by analyzing the urine for free and total hydroxyproline. In addition the hydroxyproline of the neutral salt and citrate soluble fractions of the skin was determined. Both free and total hydroxyproline were equally increased in the urine after the administration of L‐thyroxine. The increase was of the same magnitude in two, four and twelve months old rats, although the basal excretion values of hydroxyproline were significantly lower i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

1965
1965
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…Hydroxyproline concentration determination for total collagen content was performed in kidney lysates as described from Kivirikko et al [31]. Briefly, tissue was lysed in 1% Triton, 4 mM EDTA, 1% protease inhibitor cocktail II (Sigma Chemicals) and homogenized with a prechilled mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%
“…Hydroxyproline concentration determination for total collagen content was performed in kidney lysates as described from Kivirikko et al [31]. Briefly, tissue was lysed in 1% Triton, 4 mM EDTA, 1% protease inhibitor cocktail II (Sigma Chemicals) and homogenized with a prechilled mortar and pestle.…”
Section: Methodsmentioning
confidence: 99%
“…Such a mechanism might explain the only slight increase in hydroxyproline excretion in our patient (Case 12, Table I) after the injection ofgrowth hormone. Kivirikko et al (1963Kivirikko et al ( , 1967a and Kivirikko, Koivusalo, and Laitinen (1964) consider that the low hydroxyproline excretion in hypothyroid Hydroxyproline excretion in various forms of growth failure individuals may be due to decreased synthesis of collagen in addition to diminished catabolism. and Mirouze et al (1971) found a good correlation between PBI levels and urinary hydroxyproline excretion.…”
Section: Resultsmentioning
confidence: 99%
“…Increased rates of hydroxyproline excretion has been observed in hyperthyroidism (13) and in patients after administration of thyroid hormone ( 14). Conversely, decreased levels of hydroxyproline excretion have been reported in patients with hypothyroidism ( 1 5 ) and in animals with experimental h y pthyroidism ( 16).…”
Section: Conversion Of Proline-u-lx' Into W O mentioning
confidence: 95%